Small crickets of New Zealand (Orthoptera: Grylloidea: Trigonidiidae and Mogoplistidae), with the description of two new genera and species - Hegg, Danilo (European Journal of Taxonomy, 2024)
Crickets (Order Orthoptera, Infraorder Gryllidea) are under-represented in New Zealand, with a total of eight species identified and formally described thus far. These include three endemic species in the family Trigonidiidae: the trig Trigonidium (Metioche) maoricum (Walker, 1869) and the ground crickets Bobilla nigrova (Swan, 1972) and B. bigelowi (Swan, 1972). Scaly crickets (family Mogoplistidae) are naturally absent in New Zealand, but one species, Ornebius aperta Otte & Alexander, 1983, has established after introduction from Australia in the 1970s. In this work, I re-examine the small crickets (families Trigonidiidae and Mogoplistidae) from New Zealand based on 368 specimens collected throughout the country, their morphology, and their song. In the subfamily Nemobiinae, I provide new diagnostic characters to discriminate between the two native species in the genus Bobilla Otte & Alexander, 1983. Additionally, I identify two species in the genus Pteronemobius Jacobson, 1904; these are P. truncatus (Saussure, 1877) and P. cf. arima Otte & Alexander, 1983, both of which are believed to be recent arrivals from Australia. The latter had been thus far undetected in New Zealand. Finally, I describe two new species of mute Nemobiinae belonging to new monotypic genera, Austronemobius chelatus gen. et sp. nov. and Mutonemobius marmoratus gen. et sp. nov. In the subfamily Trigonidiinae, the species Trigonidium (Metioche) maoricum is moved back to the subgenus Trigonidium (Trigonidium) Rambur, 1838 based on morphology. Amended descriptions are provided for this genus and species. The Australian species Trigonidomorpha sjostedti Chopard, 1925 is synonymised with Trigonidium australianum (Chopard, 1925), and the genus Trigonidomorpha Chopard, 1925 is synonymised with Trigonidium Rambur, 1838. In the family Mogoplistidae, I show that Ornebius aperta has established in the Auckland, Waikato, Taranaki and Coromandel regions. Based on song and morphology of the male terminalia, populations in Northland may belong to a separate species, referred to in this work as Ornebius aff. aperta Otte & Alexander, 1983.